Sustainability of shallow aquifer beneath an intensive agricultural track-a case study from Western Uttar Pradesh, India - Mohammad Muqtada Ali Khan; Rashid Umar; Izrar Ahmed (2012)
Groundwater is a primary resource for irrigation, domestic and industrial purposes in most of alluvial tracks of famous Indo-Gangetic plane in India. The study area is bounded by river Krishni and hindon which forms a part of Ganga-Yamuna interfluves. Study shows over-exploitation has created an adverse impact on groundwater regime. The groundwater is being excessively abstracted from shallol aquifer, posing threat to its sustainability. Futher, an attempt has been made to calculate various components of groundwater budget and to propose relevant management plans to curb prevailing groundwater situations. The methodology proposed by Groundwater Resource Estimation Commitee (GEC 1997), with few additions, was adopted to compute the groundwater budget. Various inflows and outflows to and from the aquifer have been calculated. The recharge due to rainfall and other recharge parameters such as horizontal inflows, irrigation return flow and canal seepage were estimated. Groundwater withdrawals from the aquifer i.e through direct pumpage and subsurface outflow were calculated. The result shows deficit groundwater budget. Total groundwater recharge is 185.13 million cubic metres (Mm3), whereas the total groundwater discharge is 253.2 Mm3. Thus, change in groundwater storage is -68.07 Mm3 implies an excess utilization of 37% from aquifer in-storage. According to GEC'97, stage of groundwater development is 137% which categories the area over-exploited category. Future deterioration is expected due to uncontrolled groundwater pumping and lack of surface water irrigation. Due to ease of accessibility and assured supply, groundwater has become backbone of agriculture based economy, Subsequently, groundwater depletion is likely to bring additional economic burden to its user as pumping from deeper levels requires more energy and maintenance. This study recommends introducing strict control on groundwater abstraction in order to manage the groundwater resources in the area.